Reef Carbonate Productivity During Quaternary Sea Level Oscillations. (13th April 2018) - Husson, L.; Pastier, A.‐M.; Pedoja, K.; Elliot, M.; Paillard, D.; Authemayou, C.; Sarr, A.‐C.; Schmitt, A.; Cahyarini, S. Y.
Abstract: Global variations in reef productivity during the Quaternary depend on external parameters that may alter the global chemical balance in the oceans and atmosphere. We designed a numerical model that simulates reef growth, erosion, and sedimentation on coastlines undergoing sea level oscillations, and uplift or subsidence. We further develop a probabilistic evaluation that accounts for variable vertical ground motion, erosion, and foundation morphologies. Absolute sea level change appears primordial, as productivity must have increased by an order of magnitude since the onset of the glacial cycles, ∼2.6 Ma. But most important is relative sea level change, i.e., eustasy modulated by uplift or subsidence, that rejuvenates the accommodation space and exposes pristine domains of the shore to active reefs at each cycle. Integrated over the long‐term, vertical land motion sets the pace of reef growth: productivity in tectonically unstable domains is thus expected to be up to 10 times higher than in stable regions, if any. We quantify the global length of reef coasts and the probability density functions for slopes and uplift rates. Productivity waxes during transgressions to reach 2–8 Gt CaCO 3 / yr and wanes during highstands, which may contribute to increase atmospheric p CO2 by several tens of ppm during deglaciations. Over the last 1.5 Ma, reefs precipitated ∼0.8 × 10 6 Gt CaCO 3 (∼500 × 10 3 km 3 ), the equivalent of a 1 m‐thick layer spread over the entire surface of the Earth. This production modulates the calcium budget, for it represents some 30% of the modern Ca flux in the ocean. Key Points: Probabilistic evaluation of reef carbonate production Reef productivity primarily dictated by glacial cycles, uplift, and subsidence Quaternary coral reefs modulate the chemical budget of oceans and atmosphere